2021
DOI: 10.3390/molecules26154415
|View full text |Cite
|
Sign up to set email alerts
|

2-Aryl-6-Polyfluoroalkyl-4-Pyrones as Promising RF-Building-Blocks: Synthesis and Application for Construction of Fluorinated Azaheterocycles

Abstract: A convenient and general method for the direct synthesis of 2-aryl-6-(trifluoromethyl)-4-pyrones and 2-aryl-5-bromo-6-(trifluoromethyl)-4-pyrones has been developed on the basis of one-pot oxidative cyclization of (E)-6-aryl-1,1,1-trifluorohex-5-ene-2,4-diones via a bromination/dehydrobromination approach. This strategy was also applied for the preparation of 2-phenyl-6-polyfluoroalkyl-4-pyrones and their 5-bromo derivatives. Conditions of chemoselective enediones bromination were found and the key intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The structures of all synthesized compounds were characterized based on 1 H, 13 C NMR (see SM), and IR spectroscopy data and supported by HRMS values. Although Nunsubstituted pyridones can undergo pyridinol/pyridone tautomerism [22,23], compounds 2 and 3 exist in the pyridone form. The 1 H NMR spectra of these compounds The debenzylation of products 2a-c under the action of TMSI generated in situ in anhydrous acetonitrile from TMSCl and NaI allowed us to obtain 5-acyl-2-hetaryl substituted 3,4-HPOs 3a-c in 89-92% yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of all synthesized compounds were characterized based on 1 H, 13 C NMR (see SM), and IR spectroscopy data and supported by HRMS values. Although Nunsubstituted pyridones can undergo pyridinol/pyridone tautomerism [22,23], compounds 2 and 3 exist in the pyridone form. The 1 H NMR spectra of these compounds The debenzylation of products 2a-c under the action of TMSI generated in situ in anhydrous acetonitrile from TMSCl and NaI allowed us to obtain 5-acyl-2-hetaryl substituted 3,4-HPOs 3a-c in 89-92% yields.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of all synthesized compounds were characterized based on 1 H, 13 C NMR (see SM), and IR spectroscopy data and supported by HRMS values. Although N-unsubstituted pyridones can undergo pyridinol/pyridone tautomerism [22,23], compounds 2 and 3 exist in the pyridone form. The 1 H NMR spectra of these compounds display the presence of the characteristic pyridone H-6 singlet or doublet (J H-6,NH = 3.6-6.6 Hz) at δ 7.78-7.90 ppm and the downfield singlet or doublet of the NH group at δ 12.14-12.30 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has also been shown that an analogous procedure can be used for the synthesis of a wide range of enediones, bearing various fluorinated substituents. 41 Claisen condensation has also been used for the synthesis of polycarbonyl compounds, including ethyl 11-(4-methoxyphenyl)-2,4,6,7,9-pentaoxoundec-10-enoate 14, bearing an enedione fragment. Compound 14 was synthesized by treatment of the p-anisalacetone, acetone and ethyl oxalate mixture (1 : 1 : 2) with Na and was afterwards cyclized into the corresponding pyran 15, also wielding an enedione moiety (Scheme 13).…”
Section: Acylation By Cinnamic Acid Derivativesmentioning
confidence: 99%
“…Recently, Sosnovskikh et al 41 have reported the synthesis of 6-aryl-2-fluoroalkyl-4-pyrones 64 from the corresponding fluorinated 6-phenylhex-5-ene-2,4-diones 3 (Scheme 44). This reaction proceeded through the bromination-oxidative cyclisation-dehydrobromination sequence and could be performed in a one-pot Bose et al 95 have reported the total synthesis of a bioactive natural compound, lucidone (Scheme 47).…”
Section: Cyclisation Of 1-styryl-13-diketones Into Pyrones Pyridones ...mentioning
confidence: 99%
See 1 more Smart Citation